2013
DOI: 10.4103/0972-124x.124497
|View full text |Cite
|
Sign up to set email alerts
|

How to deal with morning bad breath: A randomized, crossover clinical trial

Abstract: Context:The absence of a protocol for the treatment of halitosis has led us to compare mouthrinses with mechanical oral hygiene procedures for treating morning breath by employing a hand-held sulfide monitor.Aims:To compare the efficacy of five modalities of treatment for controlling morning halitosis in subjects with no dental or periodontal disease.Settings and Design:This is a five-period, randomized, crossover clinical trial.Materials and Methods:Twenty volunteers were randomly assigned to the trial. Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
10
1
2
Order By: Relevance
“…This could be attributed to the fact that in Group 1 (tooth brushing) was performed by the participants which may have disrupted the formation of plaque biofilm present on the tooth surface thereby increasing the breath scores at each time interval. Similar findings were reported in previous studies carried out by Jeronimo M et al [19] and Newby et al [20]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could be attributed to the fact that in Group 1 (tooth brushing) was performed by the participants which may have disrupted the formation of plaque biofilm present on the tooth surface thereby increasing the breath scores at each time interval. Similar findings were reported in previous studies carried out by Jeronimo M et al [19] and Newby et al [20]. …”
Section: Discussionsupporting
confidence: 93%
“…At the start and at the end of all experimental periods, breath scores were measured by asking the volunteers to expel air through their mouths into a hand-held sulfide monitor, Breath Alert™ (Tanita Corporation®-Japan), according to the manufacturer’s instructions as performed previously in a study done by Pedrazzi et al and Jeronimo M et al [18,19]. …”
Section: Evaluation Criteriamentioning
confidence: 99%
“…However, the residual effect of tetrasodium pyrophosphate in the crevicular fluid may be relevant Table 1 to prevent calculus formation and maturation. Several studies have demonstrated that the combination of tooth brushing with regular flossing provides a significant improvement of oral health as a whole (23)(24)(25), but the development of a high quality preventive dental material can and should contribute to improved levels of oral health of the population. New methodologies that bring improvements over time of the active principle in crevicular fluid are required, so the production of the anticalculus effect could be maximized.…”
Section: Discussionmentioning
confidence: 99%
“…Effective halitosis treatment is believed to require the use of scrapers to remove the tongue coating and biofilm covering the tongue dorsum (12). This removal is often described as the most effective treatment for halitosis (13).…”
Section: Introductionmentioning
confidence: 99%